Co@Co3O4 Core–Shell Three‐Dimensional Nano‐Network for High‐Performance Electrochemical Energy Storage. Issue 13 (17th March 2014) - Zhang, Junli; Fu, Jiecai; Zhang, Junwei; Ma, Hongbin; He, Yongmin; Li, Fashen; Xie, Erqing; Xue, Desheng; Zhang, Haoli; Peng, Yong
<x xml:space="preserve">Abstract</x> An alternative routine is presented by constructing a novel architecture, conductive metal/transition oxide (Co@Co3O4) core–shell three‐dimensional nano‐network (3DN) by surface oxidating Co 3DN in situ, for high‐performance electrochemical capacitors. It is found that the Co@Co3O4 core–shell 3DN consists of petal‐like nanosheets with thickness of <10 nm interconnected forming a 3D porous nanostructure, which preserves the original morphology of Co 3DN well. X‐ray photoelectron spectroscopy by polishing the specimen layer by layer reveals that the Co@Co3O4 nano‐network is core–shell‐like structure. In the application of electrochemical capacitors, the electrodes exhibit a high specific capacitance of 1049 F g−1 at scan rate of 2 mV/s with capacitance retention of ∼52.05% (546 F g−1 at scan rate of 100 mV) and relative high areal mass density of 850 F g−1 at areal mass of 3.52 mg/cm2. It is believed that the good electrochemical behaviors mainly originate from its extremely high specific surface area and underneath core‐Co "conductive network". The high specific surface area enables more electroactive sites for efficient Faradaic redox reactions and thus enhances ion and electron diffusion. The underneath core‐Co "conductive network" enables an ultrafast electron transport.